Pengaruh biaya produksi terhadap keuntungan industri Roti dan Kue di Kota Palembang - Roberkat Saragih; Muhammad Teguh; Harunurrasyid Harunurrasyid (Jurnal Ekonomi Pembangunan, 2018)
This study aims to determine the cost structure and the effect of average costs on average profits of the bread and cake product industry in Palembang. The data in this study were obtained from the respondents (primary data) through observation and interview methods. The testing of the hypothesis in this study was conducted by means of the simple regression analysis and the data were processed by using e-views 8 program. The sampling technique used in this study was snowball sampling and obtained 15 business units in the bread and cake product industry in Palembang. The results showed that the biggest cost was raw materials costs with a percentage of 68.35 percent, then followed by labor costs with a percentage of 14.82 percent, the cost of auxiliary materials with a percentage of 7.72 percent, energy costs with a percentage of 5.22 percent, depreciation costs with a percentage of 3.59 percent and the smallest cost is the cost of renting a building with a percentage of 0.31 percent, while the average cost had a significant and negative effect on the bread and cake product industry in Palembang